MODERN TRENDS INFORMATIONAL TECHNO-ENABLING TECHNOLOGIES OF PROFESSIONAL COMPETENCE IN THE HIGHEST EDUCATION IN THE CONTEXT OF ANTHROPOLOGICAL DEVELOPMENT - Mudrak, V. I. (Anthropological Measurements of Philosophical Research, 2012)
Modern approaches to the anthropology development in the global information space are realized in the system of technica - echnology provision of professional competence in the highesteducation. This implies running time the newest relation systems in context “man-technetechnology- education-professional competence”.